Corruption In Uzbekistan, Political and Legal Strategy for The Fight Against It - Aliyev Bekdavlat; Sokhibjon Umarjonov (Indonesian Journal Publisher, 2025)
Corruption is one of the global problems that must be solved on a global scale. This scourge seriously undermines the political and economic development of any state and society, leading to the violation of human rights and freedoms. Therefore, the fight against it has acquired international significance and is among the important issues of world politics. The article analyzes the legislative documents on the fight against corruption in the Republic of Uzbekistan. The experience of countries with rich experience in the fight against corruption is also studied